Pravila stroke posamičnega in množičnega ocenjevanja nepremičnin pri nas in po svetu - Kožar, Anton (Podjetje in delo, 2014)
The article deals with the valuation process for taxation of property. The author explains some basic features of individual real property valuation and mass valuation for taxes. The author concludes that professional rules for individual valuation are clear in Slovenia and incorporated into the law. There are many problems in the field of application of professional rules for individual valuation. However, the existing Real Property Mass Valuation Act in Slovenia does not determine the professional rules (international or local) on which the tax administration (with cooperation with Surveying and Mapping Authority of the Republic of Slovenia) calculates the tax base (tax value of property). Moreover, the tax administration determines the rules partly in the law, partly in bylaw in conduction with the executive establishment (government), with no possibility of a remedy against the chosen valuation model. The article concludes that the independent professional institution should be established in Slovenia. It should have competence for setting rules on the valuation standards. It should also be an entity distinct from executive and taxation authority and the taxpayers should be given a possibility to check the calculation of tax base and have a regular legal remedy against it.
Keywords: davki; lastnina; nepremičnine; ocenjevanje; tax; vrednost; vrednotenje